AB1243 Getting a heeadsss in psychosocial screening: use of standardised clinic note templates for psychosocial screening in a paediatric rheumatology clinic. (12th June 2018) - Brennan Treemarcki, E.; Szymonifka, J.; Adams, A.; Pan, N.; Taber, S.; Onel, K.
Abstract : Background: Children and adolescents with rheumatic diseases are at risk for psychosocial challenges related to illness, treatment, and normal development and should receive psychosocial screening. Psychosocial assessments have been successfully utilised in other paediatric specialties, including oncology and gastroenterology. A common psychosocial screening tool is the HEEADSSS (home environment, education/employment, eating, activities, drugs, sexuality, suicide/depression, and safety). This tool is easy to remember, quickly administered, and modifiable for younger children. Objectives: We conducted a quality improvement project aimed to increase psychosocial screening by providers in a single paediatric rheumatology clinic by instituting standardised follow up templates for juvenile idiopathic arthritis (JIA) and systemic lupus erythematosus (SLE) including the HEEADSSS assessment. Methods: The quality improvement intervention evaluated in this study involved the creation of disease specific follow up note templates inclusive of the HEEADSSS assessment and introduction of the templates to the paediatric rheumatology fellows clinic. Charts of patients with an ICD-10 diagnosis of JIA or SLE were reviewed during a 3 month window prior to (February-April 2017) and after (October-December 2017) the intervention. Charts were reviewed for presence of 2 elements of the HEEADSSS assessment documented within the previous 12 months: smoking exposure (all patients) and sexual activity (ages 11 years and up). The proportion of patients with completed HEEADSSS assessment components pre- and post-intervention were compared using Fisher's exact test. Results: Chart review included 36 patients pre- and 42 post-intervention (table 1). There was an increase in assessment of both measures in the period immediately following the intervention. Assessment of smoking exposure increased from 0.0% to 21.4% (p=0.003) with greater but not significant improvement in SLE versus JIA patients (29.4% versus 16.4%, p=0.45). Assessment of sexual activity in patients 11 years and older increased from 13.0% to 37.5% (p=0.09), although this comparison may be underpowered due to decreased sample sizes. Conclusions: Introduction of standardised note templates with the HEEADSSS assessment has resulted in preliminary improvement in psychosocial screening by providers in a single paediatric rheumatology clinic as demonstrated by improved rates of screening for smoking exposure and a trend towards improved screening rates for sexual activity. Additional studies are needed to confirm these findings, and future studies will assess whether the improvement seen is sustained and whether usage of this template can be expanded to other paediatric patient populations. Acknowledgements: We thank the EMR team for helping develop the note templates and the fellows for adopting these templates. Disclosure of Interest: None declared